1999
DOI: 10.1093/hmg/8.8.1425
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Symptoms of Meniere's Disease in three Families With a Mutation in the COCH Gene

Abstract: We report the genetic analysis of one large Belgian and two small Dutch families with autosomal dominant non-syndromic progressive sensorineural hearing loss associated with vestibular dysfunction. Linkage studies in the Belgian family mapped the disease to the DFNA9 locus on chromosome 14. Mutation analysis of the COCH gene, which is responsible for DFNA9, revealed a missense mutation changing a highly conserved residue. One of the patients, who had an earlier age of onset in comparison with most of the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 19 publications
7
113
3
Order By: Relevance
“…Fransen et al 3 and Verstreken et al 6 reported a large DFNA9 family where, apart from hearing loss and vestibular dysfunction, 25% of the carriers of the COCH mutation suffered from recurrent episodes of dizziness, associated with tinnitus, aural fullness, nausea, and vomiting. Such episodes are very similar to the vertigo attacks encountered in Meniere's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fransen et al 3 and Verstreken et al 6 reported a large DFNA9 family where, apart from hearing loss and vestibular dysfunction, 25% of the carriers of the COCH mutation suffered from recurrent episodes of dizziness, associated with tinnitus, aural fullness, nausea, and vomiting. Such episodes are very similar to the vertigo attacks encountered in Meniere's disease.…”
Section: Introductionmentioning
confidence: 99%
“…COCH was chosen as a candidate for hearing loss due to its high expression in the Morton fetal cochlear cDNA library (Robertson et al, 1994;Robertson et al, 1997). Mutations in the gene have since been found to be responsible for DFNA9 in a number of families around the world (Robertson et al, 1998;de Kok et al, 1999;Fransen et al, 1999;Kamarinos et al, 2001;Usami et al, 2003;Nagy et al, 2004;Kemperman et al, 2005;Street et al, 2005;Collin et al, 2006;Pauw et al, 2007). But, although this relationship is well-established, mice deficient in Coch do not exhibit hearing loss (Makishima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…15 Combining genetic linkage analysis and positional candidate gene strategies, three different missense mutations were found in the COCH gene in three US families: V66G, G88E and W117R. 3 Subsequently, a P51S mutation was identified in one large Belgian and two small Dutch families at the DFNA9 locus, 4,19 and a fifth I109N mutation was identified in an Australian family with sensorineural hearing loss beginning in the second or third decade with concomitant vestibular dysfunction. 20 More than 25% of the patients affected with P51S mutation in the European kindreds showed episodes of vertigo, tinnitus and aural fullness with sensorineural hearing loss, which were consistent with the criteria for MD.…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations have been described in the coagulation factor C homology (COCH) gene (14q12 -13), which cause the autosomal dominant sensorineural hearing loss DFNA9 (OMIM 603196), 3 and a high prevalence of symptoms of MD has been described in three European families with a P51S mutation in exon 4 of COCH gene. 4 A group of British patients with FMD have shown an autosomal dominant inheritance with 60% penetrance, anticipation and an association with the class I HLA Cw7 antigen. 5 Linkage analysis has pointed to chromosome 14, but sequencing has excluded any mutation of the 12 coding exons of COCH gene in the British families.…”
Section: Introductionmentioning
confidence: 99%